Efficient MAC protocol for drive‐thru Internet in a sparse highway environment. Issue 3 (1st February 2017) - Li, Baozhu; Luan, Tom Hao; Hu, Bo; Chen, Shanzhi
Abstract : The demands for vehicular Internet access are proliferating. To enable vehicular communications, roadside units (RSUs) can be deployed along the roadside to provide wireless coverage and network access for driving‐thru vehicles and the performance of vehicle to RSU communications have been studied in multiple contexts. However, there is not still an efficient media access control (MAC) scheme specific for the sparse highway environment. In this study, the authors investigate the MAC scheme of drive‐thru Internet in a sparse highway environment by a Markov chain encountering model. The analytical model incorporates the high‐node mobility with the modelling of distributed coordination function (DCF) and unveils the impacts of mobility velocity and number of vehicles on the throughput. On the basis of the model, they develop a new MAC scheme and show that when vehicle number is small the proposed MAC scheme can obtain higher throughput and mitigate the impacts of vehicle mobility on the system throughput, which is desirable for the sparse highway environment. Using extensive simulations, they validate the accuracy of the analytical model and effectiveness of the proposed MAC scheme.